2008
DOI: 10.1158/1078-0432.ccr-07-4485
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Antitumor Radiation Efficacy and Consistent Induction of the Abscopal Effect in Mice by ECI301, an Active Variant of Macrophage Inflammatory Protein-1α

Abstract: Purpose: We studied whether i.v. administration of a chemokine after local tumor site irradiation could prevent remaining, as well as distant, nonirradiated tumor cell growth by leukocyte recruitment. Experimental Design: Tumors were implanted s.c. in the right or both flanks. After local irradiation at the right flank, ECI301, a human macrophage inflammatory protein-1α variant was injected i.v. Tumor volumes were measured every 3 days after treatment. Results: In Colon26 adenocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
106
0
3

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(113 citation statements)
references
References 39 publications
4
106
0
3
Order By: Relevance
“…L'effet abscopal est un phénomène très rare en clinique. Toutefois, il a été documenté chez des patients porteurs d'une grande variété de tumeurs [35] et quelques travaux ont montré que cet effet reposait sur le développement d'une immunité antitumorale spécifique [36,37]. D'autres effets antitumoraux indépendants de l'irradiation de la cible ont pu être caractérisés et plusieurs études ont mis en évidence les différents mécanismes par lesquels la radiothérapie stimulait le système immunitaire.…”
Section: Radioimmunothérapie a Et Immunité Antitumoraleunclassified
“…L'effet abscopal est un phénomène très rare en clinique. Toutefois, il a été documenté chez des patients porteurs d'une grande variété de tumeurs [35] et quelques travaux ont montré que cet effet reposait sur le développement d'une immunité antitumorale spécifique [36,37]. D'autres effets antitumoraux indépendants de l'irradiation de la cible ont pu être caractérisés et plusieurs études ont mis en évidence les différents mécanismes par lesquels la radiothérapie stimulait le système immunitaire.…”
Section: Radioimmunothérapie a Et Immunité Antitumoraleunclassified
“…Opinion is divided as to the ability of ionizing radiation to generate the signals required for DC maturation; however, the combined approach of inducing cell death by irradiation in combination with the administration of a chemotactic agent that activates DCs can lead to the priming or enhancement of antitumor responses (Shiraishi, et al, 2008).…”
Section: Possible Mechanisms Via DC Activationmentioning
confidence: 99%
“…Myelosuppressive effect of the active variant (Arango, et al, 1999,Arango, et al, 2001,Gilmore, et al, 1999,Lord, et al, 1995 was investigated in several clinical trials of patients receiving chemotherapy (Bernstein, et al, 1997,Broxmeyer, et al, 1998,Clemons, et al, 1998,Marshall, et al, 1998. We previously showed that the recombinant MIP-1 variant, now called ECI301, strikingly enhanced the antitumor efficacy of subcutaneous tumor irradiation and induced an abscopal effect (Shiraishi, et al, 2008). Our study resulted in tumor-free mice with long-term survival without significant toxicity and complete rejection by surviving mice to a re-challenge with the same tumor cells.…”
Section: Attempts To Consistently Induce the Abscopal Effectmentioning
confidence: 99%
“…In fact, unstable L forms of bacteria can often be isolated from patients with chronic respiratory tract infections who have been treated with cell wall-affecting antibiotics*. 2 Before publishing our first paper on a potential new antitumor treatment, 3 the authors of this article had studied the function of leukocytes and immune-compromised hosts, especially patients with phagocyte disorders. Whether disorders were caused by congenital defects in their function 4,5 or by secondary defects like opsonin deficiency, 6 the patients suffered from recurrent life-threatening infections, and infection control of these patients was difficult using antibiotics.…”
mentioning
confidence: 99%
“…The results of the model experiments showed striking inhibition of tumor growth with complete tumor eradication from about half of the mice, as well as consistent induction of the abscopal effect. 3 The limitations in radiation therapy could thus be overcome, and the remaining cells considered eradicated by immune reaction, since depletion of various leukocytes reversed the suppression effect of eMIP. Administration of docetaxel also spoiled the suppressive effect of radiation and eMIP, suggesting that the immune reaction was inhibited by the chemotherapeutic agent.…”
mentioning
confidence: 99%